2017
DOI: 10.1016/j.jor.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Tibioplasty, a new technique in the management of tibial plateau fracture: A multicentric experience review

Abstract: Balloon-tibioplasty represents an improved and accurate modality for restoration of articular congruence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
(8 reference statements)
1
9
0
Order By: Relevance
“…Complications of ORIF surgery can be muscular damage, postoperative pain and swelling, infection, operation time, scarring, and damage to the blood supply to the periosteum. 9 These evidences encouraged the use of percutaneous reduction with balloon and cement augmentation in tibial plateau fractures, a technique derived from vertebral surgery but also used successfully in maxillofacial surgery and for the treatment of calcaneus, 10 cuboid, 11 distal radius, 12 and acetabular 13 . Reiley, 14 in 2003, first described this technique for the tibial plateau.…”
Section: Discussionmentioning
confidence: 99%
“…Complications of ORIF surgery can be muscular damage, postoperative pain and swelling, infection, operation time, scarring, and damage to the blood supply to the periosteum. 9 These evidences encouraged the use of percutaneous reduction with balloon and cement augmentation in tibial plateau fractures, a technique derived from vertebral surgery but also used successfully in maxillofacial surgery and for the treatment of calcaneus, 10 cuboid, 11 distal radius, 12 and acetabular 13 . Reiley, 14 in 2003, first described this technique for the tibial plateau.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium sulphate, calcium phosphate (CaP) ceramics and injectable cements and bio-active glass, represent the more used synthetic bone substitutes. These composites share similar mechanical characteristics, aiming to imitate the osteoconductive function of autografts and allografts, and are mainly used to fill the void in large segmental defects [5,44].…”
Section: Bone Substitutesmentioning
confidence: 99%
“…These early studies showed a low incidence of complications and satisfactory clinical and radiological results. (6)(7)(8)(9) A thorough understanding of the clinical and imaging anatomy of the tibial plateau and the tibial plateau is essential when trying to perform less invasive surgery on intraarticular plateau fractures. All these new technologies have achieved good clinical results.…”
mentioning
confidence: 99%